Present and past hydroecology of the Old Crow Flats, YT, 2007-2011 - Nagwan, Lance; Wolfe, Brent (Canadian Cryospheric Information Network, 2011)
Water samples are being collected from ~50 basins and 13 river locations at three time steps during the thaw season for analysis of water chemistry, stable isotope composition, total suspended sediment concentration, phytoplankton and zooplankton. Sampling began in 2007 and will continue through 2011. In 2007 at six lakes, data loggers were installed to obtain continuous records of lake level changes and periphyton samplers were deployed to characterize benthic algae and provide information about water-quality and ecological conditions. An evaporation pan and meteorological station have been established at the Old Crow airport to constrain isotope-mass balance modelling of lake water isotope compositions. : Purpose: The hydroecological research initiative described here comprises one of many components of a multidisciplinary and collaborative research program supported by the Government of Canada International Polar Year (IPY) Program. Furthering knowledge of the hydroecology of OCF ecosystem is central to addressing concerns expressed by the community of Old Crow and will contribute to the Park Management Plan for Vuntut National Park. Research will assess the relative importance of hydrological processes that govern present-day lake water balances and whether currently declining lake levels represent a unique directional change or reflect natural hydrological variability. Contemporary hydrological variability in the OCF will be determined using water isotope tracers. Parallel studies will characterize the limnological conditions of the lakes and identify relationships between water chemistry and basin hydrology. Records of hydroecological variability over decadal to centennial timescales will be derived from multi-proxy analysis of lake sediment cores obtained from selected basins in the OCF. : Summary: Not Applicable